STUDY REGARDING THE PROFESSIONAL MOTIVATION IN PHYSICAL EDUCATION AND SPORTS STUDENTS - Gloria RAȚĂ; Tatiana DOBRESCU; Bogdan Constantin RAȚĂ; Marinela RAȚĂ; G MAREȘ (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2011)
The knowledge of the professional motivation that determines the efficiency of the didactic training in studentsconstitutes a starting point in treating each individual's personality. For this reason, we initiated a study on 26 secondyear Physical Education students, which had as an assessment instrument "professional motivation questionnaire".Following data analysis we saw that the students have professional reasons differently enclosed in the 5 groups ofmotives and needs. For our group, the ones that have priority are the needs and reasons involving human socialcontacts, with a value of 108.12 points, the ones regarding self-accomplishment with an average value of 111.54 points,followed by esteem and consideration with an average value of 122.92, by the ones involving security with 138.88 andfinally the ones involving physiology with 149.35 points. The results emphasize the maturity and the responsibility ofthe studied subjects. Each individual from the group is an individual personality who has his/her own professionalmotivation; therefore we treated them individually during the didactic act of professional training, taking into accounteach student's particularities.